2017
DOI: 10.1155/2017/4965816
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Positive Thinking Training Program on Nurses’ Quality of Work Life through Smartphone Applications

Abstract: Aim Job stress is a part of nurses' professional life that causes the decrease of the nurses' job satisfaction and quality of work life. This study aimed to determine the effect of positive thinking via social media applications on the nurses' quality of work life. Methods This was a pretest-posttest quasi-experimental study design with a control group. The samples were selected among the nurses in two hospitals in Fasa University of Medical Sciences and divided randomly into two interventional (n = 50) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 26 publications
2
67
0
2
Order By: Relevance
“…In other words, more experienced nurses less frequently used the rumination strategies. This is in line with the findings of an earlier study which showed that nurses with limited work experience suffered from higher levels of occupational stress [33]. Another finding of the present study was the direct significant correlation of acceptance strategies with work experience so that nurses with higher work experience more frequently used this strategy.…”
Section: Discussionsupporting
confidence: 93%
“…In other words, more experienced nurses less frequently used the rumination strategies. This is in line with the findings of an earlier study which showed that nurses with limited work experience suffered from higher levels of occupational stress [33]. Another finding of the present study was the direct significant correlation of acceptance strategies with work experience so that nurses with higher work experience more frequently used this strategy.…”
Section: Discussionsupporting
confidence: 93%
“…smoking education; see below for smoking cessation interventions) or had education as an element of a more complex or combined intervention. Education provision typically related to coping with stress (n = 19) [55,59,60,65,69,72,75,76,[84][85][86]91,92,[94][95][96]102,106,110], emotion regulation (n = 8) [56,73,74,90,99,100,105,109], communication skills (n = 2) [56,89], positive thinking/positive intervention (n = 4) [79,101,103,107], searching for meaning (n = 1) [108], compassion fatigue/burnout (n = 8) [66,70,71,[80][81][82]87,93], the selection optimisation compensation (SOC) model (n = 2) [57,62], self-care (n = 5) [61,63,77,…”
Section: Educational Interventionsmentioning
confidence: 99%
“…Life (Brooks and Anderson's scale [103]), the Team Building Questionnaire [179], the Job Diagnostic Survey [108], and the Benefits of Working (Benefits Finding Scale [108]).…”
Section: Health Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations